Filantropi Islam untuk Membangun Amal Usaha Muhammadiyah: Studi Kasus Fundrising untuk Pembangunan Masjid At-Tanwir PCM Bojongsari - Kota Depok - Syaifullah, Hamli; Kartika, Rini Fatma; Dianto, Icol; Muttaqien, Muhammad Khaerul; Faisol, Moh. (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
This research is a type of qualitative descriptive research with a case study approach to Islamic Philanthropy to Build Muhammadiyah Charity Business: Case Study of Fundraising for the Construction of the At-Tanwir Mosque PCM Bojongsari-Depok City, with a focus on how to carry out effective and efficient fundraising. The data used in this research include: documentation and observation. The data that has been collected will be processed and analyzed using the Miles & Huberman interactive model, which includes: (1) data collection; (2) data reduction; (3) data display; and (4) drawing conclusions from the data/or verification stage. Then, reliability and validity are carried out by, among other things: (1) carrying out careful re-checking procedures; (2) carrying out varied and comprehensive data mining techniques; and (3) increasing the number of research subjects and informants. The focus of questions in this research include: (1) What strategies did the Muhammadiyah Bojongsari Branch Leader use in raising Islamic philanthropic funds to build the At-Tanwir Muhammadiyah Bojongsari Mosque? ; and (2) Does the use of Islamic philanthropic fundraising strategies have a significant impact on raising funds to build the At-Tanwir Muhammadiyah Bojongsari Mosque? From the results of the analysis of the data, answers can be obtained, including: (1) the strategy used is to utilize the internal and external community of Bojongsari, both from Muhammadiyah and non-Muhammadiyah communities; and (2) the use of this strategy was very significant, it was proven that PCM Bojongsari was able to receive funds of more than IDR 1 billion.